DEVELOPMENT OF NUMERIC MODELS FOR COUPLER, CRASH BUFFER, AND ANTI-CLIMBER OF MERAH PUTIH HIGH-SPEED TRAIN - Fitria'Izzul Haq, Lailatul
In the development of Merah Putih High-Speed Train (KCMP) improving the quality of the safety system is a crucial aspect that must be considered, especially in dealing with potential accidents or collisions which could have a negative impact on passengers, in other words the train must have a crash-worthy design. One of the safety quality improvements that will be analyzed is the quality of the energy absorbing structure of the Coupler, Crash Buffer, and Anti-Climber components of the Crash Energy Management (CEM) system at KCMP. Trains equipped with CEM systems will manage collision energy more effectively and efficiently than conventional trains. In this research, numerical modeling will be carried out for the crashworthiness test using the finite element method for each component of the CEM system. The energy absorption characteristics of each CEM system component are represented by spring and damper elements. Several parameter variations were carried out, namely the percentage of loading on the spring, the damping constant for the damper, the distance between the gear of the anti-climber component, and the position of the placement of each component of the CEM system. The simulation results show that the damping constant value will influence the activation force and stability in energy absorption. Meanwhile, the amount of spring stiffness or in nonlinear springs in the form of defining loading and unloading from the force-length deformation curve does not have a big influence on the amount of energy absorption. From the crash test of one carriage, it was found that the average collision energy absorption by the CEM system was around 75-80% of the total energy absorbed during the collision. Apart from that, the numerical model in this research complies with EN:15227 regulations, namely having a maximum slowdown of 3.9 G where the maximum limit is 5G. However, it does not meet other requirements of the regulations, namely that there is still displacement in the vertical direction of more than 100 mm.